Comment on “Conserved phylogenetic distribution and limited antibiotic resistance of class 1 integrons revealed by assessing the bacterial genome and plasmid collection” by A.N. Zhang et al. - Roy, Paul H. (Microbiome, 2021)
An article published in Microbiome in July 2018 uses incorrect definitions of integron integrase IntI1 and of class 1 integrons that affect the interpretation of the data.